REINTERPRETASI QALB: TAFSIR ULANG MAKNA HATI SEBAGAI LOKUS SPIRITUAL DAN PENERIMA PESAN TRANSENDENTAL - Fairus Fairus (Al-Balagh : Jurnal Komunikasi Islam, 2016)
The findings of the “God Spot” (G-Spot) that is located among the brain's nerve tangle has been changed the human perception about spirituality. The phe-nomenon of G-Spot is an indication that spirituality and spiritual intelligence/spi-ritual quotient rooted in the human brain. Through the brain, human does not have the potential of emotion and rationality only, but also the potential and tools for spirituality. This reality is contrary to the traditions and belief of Muslims in Indonesia. Various classical records and spreading religious experiences believe that qalb which is often translated as liver, is the one which has a role in spiritual matters. Liver is considered as a locus of spirituality that makes one knows God and gives him the knowledge of the meaning and value. Popular references about liver spi-rituality is based on Iḥyā’ ‘Ulūm Al-Dīn by Al-Ghazālī and the ḥadīth about a pie-ce of meat in the human body that was narrated by Nu‘mān Ibn Bashīr as later narrated by Bukhārī, Muslim, and other narrators that are known for good inte-grity.This study aims to describe qalb in the tradition of the Muslims in Indonesia and its relation to contemporary findings in the field of neuroscience that puts the brain as a spiritual tool. The answer to this question is expected to reveal the meaning of the term radical qalb: which one of brain and liver that is more rele-vant to be interpreted as qalb? Or maybe something else? Patterned library re-search, the approach used in this study is rationalistic abstractive, simple, and al-low rational meaning of the object of study. The grounds are concerned with as-pects of contemporary, thought patterns used are reflective contextual.The study shows that the Muslims who live and interact in Indonesian culture in Indonesia mistakenly understood the meaning of qalb, as Al-Ghazālī wrote 915 years ago. Qalb is meant in the ḥadīth Nu‘mān Ibn Bashīr nor liver (hepar) or brain (encephalon), but heart (cardiac). Anatomical aspects in this study conclude that human spirituality center is located in the heart (cardiac). Statement of Allah in Sūrah Al-Ḥajj verse 46 a signal about the position and the potential of the heart (cardiac) as a piece of meat called qalb which has the ability to understand, recog-nize, and feel the spiritual consciousness. This device functions as a locus of hu-man receive transcendental messages.